Aspects of AdS flux vacua with integer conformal dimensions - Fien Apers (Journal of High Energy Physics, 2023)
Abstract The DGKT vacua are a class of AdS4 flux vacua showing full moduli stabilization, parametric control, and a parametric separation of scales. The particular masses of the moduli remarkably give rise to integer conformal dimensions in the light spectrum of the would-be holographic duals. In this note, we comment on two properties for AdS flux vacua with integer conformal dimensions. First, there are polynomial spacetime-dependent shift symmetries for the moduli. Secondly, the leading scalings of the central charge and the moduli can be directly deduced from the near-horizon geometry of stacks of orthogonally-intersecting D-brane domain walls dual to the unbounded fluxes. This suggests that a dual field theory could be found on this relatively simple set of domain walls. We illustrate this in a couple of examples of AdS4 and AdS3 parametric flux vacua.